Cement-free Yellow River sediment autoclaved aerated concrete block and preparation method thereof

By using solid waste such as Yellow River silt and slag powder, and forming gelled materials through alkaline excitation, the performance problems of fly ash concrete blocks and the high cement cost in the existing technology are solved, and the preparation of low-carbon high-value autoclaved aerated concrete blocks without cement is realized.

CN119874306APending Publication Date: 2025-04-25YELLOW RIVER INST OF HYDRAULIC RES YELLOW RIVER CONSERVANCY COMMISSION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510049687.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the autoclaved aerated concrete blocks with fly ash as the main raw material have problems of strength, durability, hollowing and cracking. At the same time, the cost of using cement is high, which is not conducive to promotion.

Method used

Solid waste such as Yellow River silt, slag powder, ash powder and other solid wastes are used as raw materials to generate gelled materials through alkaline excitation to prepare cementless autoclaved aerated concrete blocks.

Benefits of technology

The preparation of low-carbon, high-value, high-quality and low-priced autoclaved aerated concrete blocks has been achieved, which has digested a large amount of environmentally unfavorable waste, reduced carbon emissions, and improved the strength and durability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874306A_ABST
    Figure CN119874306A_ABST
Patent Text Reader

Abstract

The invention relates to a cement-free Yellow River sediment autoclaved aerated concrete block and a preparation method thereof. The concrete block is prepared from solid wastes such as the Yellow River silt, the slag powder and the ash powder as raw materials, and cement does not need to be added in the preparation process. The Yellow River silt is used as a main siliceous material instead of quartz sand, so that the cost can be effectively reduced; cement is not used in the raw materials, carbon emission can be reduced, meanwhile, the waste incineration ash powder is introduced into the aerated concrete, and secondary pollution of the waste incineration ash to the ecological environment can be effectively avoided. The cement-free Yellow River sediment autoclaved aerated concrete block disclosed by the invention is excellent in performance, and has good physical and mechanical properties and durability, and the performance indexes all meet the standard requirements of autoclaved aerated concrete blocks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid waste resource utilization, and in particular to a cement-free Yellow River sediment autoclaved aerated concrete building block and a preparation method thereof. Background Art

[0002] At present, concrete blocks on the market are made of fly ash as the main raw material, with quicklime, cement and other admixtures. The raw fly ash is fine ash collected from the flue gas after coal combustion. The quality of fly ash is prone to instability, which will lead to the decline of the strength and durability of autoclaved aerated concrete blocks. In addition, fly ash autoclaved aerated concrete masonry is prone to hollowing and cracking.

[0003] For example, the autoclaved aerated concrete blocks in the prior art use fly ash, quicklime, gypsum, carbide slag, tailings, mud, sand, cement and the like as main raw materials, with appropriate amounts of gas generating agents, regulators and bubble stabilizers added, and are prepared through processes such as batching and mixing, pouring, static stopping and high-pressure steaming. The porous lightweight concrete block products have the characteristics of light weight, heat preservation and thermal insulation. The main raw materials used in this method contain cement components, which have a relatively high cost and are not conducive to promotion.

[0004] In recent years, the state has attached great importance to the resource utilization of the Yellow River sediment, formulated relevant laws and policies to guide the comprehensive disposal and utilization of multiple channels, and promoted scientific and technological innovation to achieve the scientific utilization of the Yellow River sediment. At the same time, the investigation, assessment and rational development of the Yellow River sediment have been strengthened to ensure the sustainable utilization of resources. Improving the efficiency of resource utilization of the Yellow River sediment is of great significance to promoting the sustainable development of local economy and society and protecting water resources and ecological environment.

[0005] How to utilize the Yellow River silt as the main raw material, use solid wastes such as slag powder and garbage incineration ash powder as admixtures, do not use cement in the preparation process, and generate cementitious materials through alkali activation of the Yellow River silt and admixtures to prepare low-carbon, high-value, high-quality and low-cost autoclaved aerated concrete block products, is the technical problem that the present invention needs to solve. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a cement-free Yellow River silt autoclaved aerated concrete block and a preparation method thereof.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A cement-free Yellow River sediment autoclaved aerated concrete block, the raw materials of which are, by weight, 610-635 parts of Yellow River sediment, 116-250 parts of slag powder, 44-80 parts of quicklime, 0-45 parts of ash powder, 0.81-1.2 parts of aluminum powder, 0.1-0.5 parts of water reducing agent, 1-2 parts of surfactant and 234-287 parts of water.

[0009] The median particle size of the Yellow River sediment is 0.08-0.15 mm, and the main chemical composition is: SiO2 60-72%, Al2O3 10-18%, CaO 3-10%, Fe2O3 2-6%, MgO 1-3%, K2O 2-3%, Na2O 1.5-3%, TiO2 0.5-2%.

[0010] The slag powder is S95 grade slag powder with a median particle size of 0.013 mm and a main chemical composition of: CaO 41-44%, SiO 2 29-32%, Al 2 O 3 14-16%, MgO 7.2-7.8%, SO 3 2-3%, TiO 2 1.25-1.35%, MnO 0.30-0.40%, Fe 2 O 3 0.25-0.35%, K 2 O 0.30-0.40%, and Na 2 O 0.25-0.30%.

[0011] The median particle size of the ash powder is 0.033 mm, and the content of the main chemical component Al2O3 is 87%; the median particle size of the aluminum powder is 0.017 mm.

[0012] The water reducer is a polycarboxylic acid water reducer, and the surfactant is fatty acid diethanolamide.

[0013] The method for preparing the cement-free Yellow River sediment autoclaved aerated concrete blocks comprises the following steps:

[0014] (a) Mix the Yellow River silt, slag powder and ash powder evenly;

[0015] (b) adding water according to the mixing ratio and stirring evenly;

[0016] (c) adding quicklime, water reducing agent and surfactant, mixing well and letting stand for 10 minutes;

[0017] (d) adding aluminum powder to the slurry and stirring until a uniform slurry is formed;

[0018] (e) Pour the slurry into the sample mold, and then place the sample mold in a curing box at 45-50°C for 3-6 hours. During this time, the slurry will foam into a sample with stable volume;

[0019] The above samples were placed in an autoclave at 150°C to 180°C and 1.0 MPa for autoclave curing for 6 to 8 hours.

[0020] Beneficial effects of the present invention:

[0021] (1) The present invention uses Yellow River silt, slag powder, and ash powder solid waste as raw materials to prepare concrete blocks, which can digest a large amount of waste that is unfavorable to the environment. At the same time, no cement needs to be added during the preparation process, which is a green and environmentally friendly concrete block production method.

[0022] The present invention adopts waste incineration ash powder as raw material, which can not only solve the environmental problems caused by waste incineration ash storage and realize waste recycling, but also use Yellow River sediment instead of quartz sand as the main siliceous material, which is more conducive to the sustainable development of the economy and society while effectively reducing costs.

[0023] (2) Since the Yellow River silt has the characteristics of fine particles and high mud content, its application scope is limited. It cannot be directly used as construction sand in the field of concrete configuration, and can only be mixed with machine-made sand as a commercial concrete raw material. At the same time, the Yellow River silt has a high SiO2 content and has a certain volcanic ash activity. The present invention uses alkali-activated slag to replace cement, and at the same time, it activates the Yellow River silt to participate in the hydration gel reaction as a cementitious material. The fine-grained silt has a large specific surface area and a better alkali activation effect. It reacts with alkali to generate hydrated calcium silicate, etc., which gives strength to aerated concrete, and can effectively reduce the adverse effects of fine-grained silt on concrete performance.

[0024] (3) The present invention avoids using cement as raw material, which can reduce carbon emissions. At the same time, the waste incineration ash powder is introduced into aerated concrete, which can effectively avoid secondary pollution of the ecological environment caused by the waste incineration ash.

[0025] (4) The main chemical components of the Yellow River silt of the present invention are SiO2 and Al2O3, among which the active parts of SiO2 and Al2O3 can undergo hydration reaction in an alkaline environment to generate hydrated calcium silicate, hydrated calcium aluminate, and hydrated calcium silicate aluminate gel, which can give the material a certain strength. The Yellow River silt particles are fine, with a large specific surface area, and the hydration reaction rate is faster and more thorough, which is conducive to improving the strength of the product. The Yellow River silt that has not undergone hydration reaction can be used as aggregate to play a supporting role.

[0026] (5) In the present invention, alkali-activated slag is used to replace cement as the main cementitious component. In an alkaline environment, the covalent bonds such as ≡Si-O-Si≡, ≡Al-O-Al≡, and ≡Si-O-Al≡ in SiO2 and Al2O3 are opened, and the internal Ca 2+ 、AlO3 3- 、SiO4 4- The plasma is released and the reaction proceeds in a polycondensation manner to form C-(A)-SH gel, which gives the product higher strength through bonding and hardening functions.

[0027] (6) The main chemical component of the ash powder used in the present invention is Al2O3. In an alkaline environment, the ≡Al-O-Al≡ bond in the active Al2O3 in the ash powder is opened, participating in the hydration and gelation reaction, thereby promoting the improvement of product strength.

[0028] (7) The function of the aluminum powder used in the present invention is to generate gas. The aluminum powder can generate gas through an oxidation reaction to form fine bubbles. The gas generation reaction of the aluminum powder proceeds together with the thickening and hardening of the concrete slurry, thereby forming a concrete masonry structure with a pore structure. These pore structures can reduce the density of the concrete and make it lightweight.

[0029] 2Al+6H2O=2Al(OH)3+3H2

[0030] 2Al+3Ca(OH)2+6H2O=3CaO·Al2O3·6H2O+3H2

[0031] (8) The Yellow River silt used in the present invention has not been subjected to pre-treatment processes such as screening and desludging, and is easy to operate and saves costs.

[0032] (9) The autoclaved aerated concrete blocks prepared by the method of the present invention have excellent performance, good physical and mechanical properties and durability. The compressive strength is 3.10MPa-4.29MPa, and the dry density is 615kg / m 3 ~649kg / m 3 The drying shrinkage value is 0.42~0.47mm / m, the frost resistance mass loss is 0.54%~0.89%, and the frost resistance strength loss is 8.65%~10.43%. The performance indicators all meet the requirements of the "Autoclaved Aerated Concrete Block" (GB / T 11968-2020) standard. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 XRD pattern of the Yellow River sediment autoclaved aerated concrete blocks;

[0034] Figure 2 XRD pattern of Yellow River sediment;

[0035] Figure 3 XRD pattern of slag. DETAILED DESCRIPTION

[0036] The specific implementation methods of the present invention are further described in detail below in conjunction with the examples. Unless otherwise specified, the instruments and equipment involved in the examples are all conventional instruments and equipment, the raw materials involved are all commercially available conventional raw materials, and the test methods involved are all conventional methods.

[0037] Example 1. A cement-free Yellow River sediment autoclaved aerated concrete block and its preparation method

[0038] 1. Raw material composition: 635 parts of Yellow River silt, 125 parts of slag powder, 45 parts of quicklime, 0.81 parts of aluminum powder, 0.5 parts of water reducer, 2 parts of surfactant, and 234 parts of water.

[0039] The Yellow River sediment is selected from the Zhengzhou section, the median particle size of the sediment is 0.08-0.15 mm, and its main chemical composition is SiO2 60-72%, Al2O3 10-18%, CaO 3-10%, Fe2O3 2-6%, MgO 1-3%, K2O 2-3%, Na2O 1.5-3%, TiO2 0.5-2%. The mineral composition of the Yellow River sediment can be seen in Figure 2 It can be seen that the minerals contain quartz, plagioclase, and calcium carbonate.

[0040] The quicklime meets the requirements of "Quicklime for Silicate Building Products" (J / CT 621).

[0041] The slag powder was purchased from Qianhao Mineral Products Processing Plant in Lingshou County, Hebei Province. It is S95 grade slag powder with a median particle size of 0.013 mm. The main chemical composition is: CaO 41-44%, SiO2 29-32%, Al2O3 14-16%, MgO 7.2-7.8%, SO3 2-3%, TiO2 1.25-1.35%, MnO 0.30-0.40%, Fe2O3 0.25-0.35%, K2O 0.30-0.40%, and Na2O 0.25-0.30%.

[0042] The mineral composition of slag is shown in Figure 3 ,from Figure 3 It can be seen that there is a large "mantou peak" between 20 and 40° in the whole spectrum, and there is also very little chalcite phase, which is a solid solution of chalcite (Ca2Al2SiO7) and chalcite (Ca2MgSi2O7). In addition, there are no other obvious crystal peaks, so it can be considered that the slag is all glassy material.

[0043] The ash powder is taken from the ash produced after the incineration of garbage in the Lankao garbage incineration plant in Kaifeng. The ash is ball-milled for 3 hours to form ash powder with a median particle size of 0.033 mm and a main chemical component Al2O3 content of 87%.

[0044] The median particle size of the aluminum powder is 0.017 mm.

[0045] 2. Preparation method: Weigh the mud, sand and slag powder according to the ratio and mix them evenly; add water according to the ratio and continue stirring for 90s; add quicklime, water reducer and surfactant and mix evenly, and let it stand for 10 minutes; add aluminum powder to the slurry and stir for 1 to 2 minutes to form a uniform slurry; pour the slurry into the sample mold, put the sample mold into a 50℃ curing box for 3 hours, and the slurry will foam into a sample with stable volume. Remove the test mold and put the demolded sample into an autoclave at 180℃ and 1.0MPa for autoclave curing for 8 hours.

[0046] Example 2. A cement-free Yellow River sediment autoclaved aerated concrete block and its preparation method

[0047] Raw material composition: 635 parts of Yellow River silt, 250 parts of slag powder, 60 parts of quicklime, 0.95 parts of aluminum powder, 0.5 parts of water reducer, 1 part of surfactant, and 274 parts of water.

[0048] The properties and requirements of each raw material are the same as those in Example 1, and the preparation method is the same as that in Example 1.

[0049] Example 3. A cement-free Yellow River sediment autoclaved aerated concrete block and its preparation method

[0050] Raw material composition: 635 parts of Yellow River silt, 166 parts of slag powder, 80 parts of quicklime, 0.88 parts of aluminum powder, 0.5 parts of water reducer, 1 part of surfactant, and 255 parts of water.

[0051] The properties and requirements of each raw material are the same as those in Example 1, and the preparation method is the same as that in Example 1.

[0052] Example 4. A cement-free Yellow River sediment autoclaved aerated concrete block and its preparation method

[0053] Raw material composition: 610 parts of Yellow River silt, 250 parts of slag powder, 80 parts of quicklime, 25 parts of ash powder, 0.99 parts of aluminum powder, 0.5 parts of water reducer, 1 part of surfactant, and 287 parts of water.

[0054] The properties and requirements of each raw material are the same as those in Example 1, and the preparation method is the same as that in Example 1.

[0055] Example 5. A cement-free Yellow River sediment autoclaved aerated concrete block and its preparation method

[0056] Raw material composition: 635 parts of Yellow River silt, 166 parts of slag powder, 44 parts of quicklime, 45 parts of ash powder, 1.2 parts of aluminum powder, 0.5 parts of water reducer, 1 part of surfactant, and 250 parts of water.

[0057] The properties and requirements of each raw material are the same as those in Example 1. In the preparation method, the pre-curing time is 3 h, the steaming temperature is 170° C., and other conditions are the same as those in Example 1.

[0058] The products obtained in Examples 1-5 were performance tested according to the standard "Autoclaved Aerated Concrete Performance Test Method" (GB / T11969-2020), and the results are shown in Table 1.

[0059] Table 1 Autoclaved aerated concrete block performance indicators of the embodiment

[0060]

[0061] The reason why the compressive strength and dry density of different embodiments are quite different is that the amounts of admixtures, alkali activators and aluminum powder in the mix are different. The compressive strength of the blocks tends to increase gradually with the increase of the amounts of admixtures and alkali activators, while the dry density of the blocks decreases gradually with the increase of the amounts of aluminum powder and water. The dry density will also affect the compressive strength of the blocks. The lower the dry density, the lower the compressive strength. Therefore, the performance differences among different embodiments are quite large.

[0062] The XRD spectrum of the Yellow River sediment autoclaved aerated concrete obtained in Example 1 of the present invention is as follows: Figure 1 The XRD patterns obtained in other embodiments are similar to this figure.

[0063] from Figure 1 It can be seen that SiO2 and Al2O3 in the Yellow River silt and slag undergo hydration reaction in an alkaline environment, and the main products of the hydration reaction are zeolite (ZSM), tobermorite, cancrystal (Yoshiokaite), hydrogrossular (katoite), CSH gel, and sodium silicate. In addition to the hydration products generated by the reaction, quartz is still the main content in aerated concrete, and the crystal form is complete, indicating that quartz not only participates in the hydration reaction, but also plays a supporting role as an aggregate. The content of the main components of the hydration products, tobermorite, cancrystal, and hydrogrossular is greater than that of CSH gel. Tobermorite, cancrystal, and hydrogrossular usually exist in the form of crystals. Although they contain some water inside, this part of water is difficult to evaporate and is generally not affected by drying. The water in the CSH gel is very easy to evaporate, causing the block to dry and shrink.

Claims

1. A cement-free Yellow River sediment autoclaved aerated concrete block, characterized in that: Calculated by weight, the raw material composition is: 610-635 parts of Yellow River silt, 116-250 parts of slag powder, 44-80 parts of quicklime, 0-45 parts of ash powder, 0.81-1.2 parts of aluminum powder, 0.1-0.5 parts of water reducer, 1-2 parts of surfactant, and 234-287 parts of water.

2. The cement-free Yellow River sediment autoclaved aerated concrete block according to claim 1, characterized in that: The median particle size of the Yellow River sediment is 0.08-0.15 mm, and the main chemical composition is: SiO2 60-72%, Al2O3 10-18%, CaO 3-10%, Fe2O3 2-6%, MgO 1-3%, K2O 2-3%, Na2O 1.5-3%, TiO2 0.5-2%.

3. The cement-free Yellow River sediment autoclaved aerated concrete block according to claim 1, characterized in that: The slag powder is S95 grade slag powder with a median particle size of 0.013 mm and a main chemical composition of: CaO 41-44%, SiO2 29-32%, Al2O3 14-16%, MgO 7.2-7.8%, SO3 2-3%, TiO2 1.25-1.35%, MnO 0.30-0.40%, Fe2O3 0.25-0.35%, K2O 0.30-0.40%, and Na2O 0.25-0.30%.

4. The cement-free Yellow River sediment autoclaved aerated concrete block according to claim 1, characterized in that: The ash powder has a median particle size of 0.033 mm, and a main chemical component, Al2O3, content of 87%.

5. The cement-free Yellow River sediment autoclaved aerated concrete block according to claim 1, characterized in that: The median particle size of the aluminum powder is 0.017 mm.

6. The cement-free Yellow River sediment autoclaved aerated concrete block according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer, and the surfactant is fatty acid diethanolamide.

7. A method for preparing the cement-free Yellow River sediment autoclaved aerated concrete block according to any one of claims 1 to 6, characterized in that: The following steps are involved: (a) Mix the Yellow River silt, slag powder and ash powder evenly; (b) adding water according to the mixing ratio and stirring evenly; (c) adding quicklime, water reducing agent and surfactant, mixing well and letting stand for 10 minutes; (d) adding aluminum powder to the slurry and stirring until a uniform slurry is formed; (e) Pour the slurry into the sample mold, and then place the sample mold in a curing box at 45-50°C for 3-6 hours. During this time, the slurry will foam into a sample with stable volume; The above samples were placed in an autoclave at 150°C to 180°C and 1.0 MPa for autoclave curing for 6 to 8 hours.